The Laurie Berkner songbook - Berkner, Laurie (Amsco Publications : Distributors, Music Sales Corporation, 2007)
Play Laurie Berkner's songs with this compilation of 25 favorites specially arranged for easy piano, voice and guitar including activity and play suggestions.